A Linear 0.98 mV Low-Dropout Voltage Regulator in 0.18-m CMOS Technology - Sohiful Anuar, Zainol Murad; Azizi, Harun; M.N.M, Isa; Arjuna, Marzuki; Rohana, Sapawi (IOP Publishing Ltd, 2021)
This paper presents a linear low-dropout (LDO) voltage regulator in 0.18-µm CMOS technology. The proposed LDO consists of voltage reference, error amplifier, pass device, output capacitor and resistive feedback network. A symmetrical operational transconductance amplifier (OTA) is implemented as an error amplifier and a PMOS transistor is used as a pass device to produce low dropout voltage and low quiescent current. The proposed design is simulated using Spectre simulator in Cadence software to verify its performances. The simulation results indicated that the LDO regulator achieves a regulated output voltage of 1.5 V with the ranges of supply voltage from 1.7 V to 2.0 V. The LDO regulator has a dropout voltage of 19.3 mV under maximum load current of 1.1 mA. The proposed LDO regulator is suitable for power management system.